Planning forest recreation: environmental economic instruments and the public participation - Oliveira, F. (2018)
In Portugal there is a growing demand for natural areas that provide a wide range of outdoor recreation. This paper focuses on the particular case of the Mata Nacional de Leiria (Leiria National Forest). This is a pine tree forest with 11,000 hectares and eight centuries of history. It has always been a public forest with open access to everyone, a fact that contributes to different kinds of use and benefits (walking, cycling, picnics, collecting firewood, fruits and berries, and other recreation activities). The proximity to a major urban and industrial centre, on one hand, and to a very popular beach coast, on the other, makes this a resource that is widely used by both residents and visitors. In the future there is the possibility of implementing a set of actions to improve forest amenities and recreation, and later the emergence of environmental tourism activities and equipment. In this context, we want to know the economic valuation that actual users attach to these recreation improvements, but also realize their preferences and opinions regarding this project. For this purpose we designed, tested and applied a double bounded dichotomous choice contingent valuation questionnaire. The results presented in this paper focus on responses to attitudinal and follow-up questions. More than 70% of respondents have positively assessed the proposed improvements to the study area and about 40% enhanced their personal opinion on the type of interventions that they consider most appropriate. Answers focus the priority areas of intervention in the Mata Nacional de Leiria, the main concerns in its development, the type of actions that should (and should not) be implemented, respondents willingness to actively take part and, also, what the public authorities' role should be. At this stage, where Mata Nacional de Leiria is being considered in terms of future recreation and tourism offers, the results obtained provide important contributions and enhance the contingent valuation survey as a tool to support recreation planning, promoting public participation and the political decision-making process.